Tantangan Kedaulatan Maritim Indonesia Dilaut Sulawesi Pasca Lepasnya Pulau Sipadan dan Ligitan - fuadillah (Journal Social Politica, 2020)
The International Court of Justice’s decision on the dispute over the islands of Sipadan and Ligitan to Malaysia’s sovereignity, while both countries (Indonesia-Malaysia) has not entered into an agreement about the border line of the two islands. The claim of Malaysia which using the map from 1979 poses a traditional and non-traditional threat, particulary in the Sulawesi Sea. The result of this research shows that there are threats related to maritime sovereignity in the Sulawesi Sea, among others prescription, illegal fishing and cross-border crime. As for Indonesia’s efforts to address these threats are by taking a diplomatic approaches and warship dispatch, improvements and additions to patrol ship, as well as the sinking of the ship and law enforcement.